COMPARISON OF HUMAN TRANSLATION WITH GOOGLE TRANSLATION OF IMPERATIVE SENTENCES IN PROCEDURES TEXT - Halimah Halimah (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2018)
AbstractThis study aims to analyze the similarity between human translation and machine translation to translate procedural text. This research uses Content Analysis approach (Content Analysis). The analysis was performed on English procedural text on a "VIXAL Lebih Wangi" cleanliness product translated into Indonesian by Nia Kurniawati (representing human translation). Meanwhile Google translation is used to represent machine translation. The study of the equations compared in this study is from the aspect of the phrase and the meaning of the whole sentence in the results of the two translations. The result of the discussion shows that the equation between human translation and machine translation in translating procedural text is low, i.e 29%. Machine translation still requires manpower to produce better translations. Keywords: equality aspect, human translation, machine translation, text procedure